Effect of Incremental Curing Agent Additions on Thermal Degradation of Polydimethylsiloxane in Air: A Kinetic Study - Falaq Muhammad Faisal, Muhammad; Ekramul Mahmud, H.N.M.; Deshannavar, U.B.; EL-Harbawi, Mohanad (Asian Journal of Chemistry, 2014)
Polydimethylsiloxane samples produced via several curing agent: Elastomer base ratios (5, 10, 15 and 20 w/w %) have been thermally degraded under air atmosphere. Thermogravimetric analysis shows that for all polydimethylsiloxane samples, the onset of significant oxidative degradation is at 290 °C and subsequently two distinct degradation stages (290-400 and 400-600 °C) can be observed. At temperatures higher than 600 °C, polydimethylsiloxane samples produced using 5, 10, 15 and 20 wt % curing agent experience weight reductions by 60, 53, 47 and 42 %, respectively. Linear regression analysis using LINEST function in Microsoft Excel indicates that data within the 290-400 °C range fit the Arrhenius model far better than the data within the 400-600 °C range. Increments in wt % curing agent from 5 to 15 % enhance the thermal stability of polydimethylsiloxane samples within the temperature range 290-400 °C.